Pressure-induced ionic liquid crystal in 1-dodecyl-3-methylimidazolium tetrafluoroborate. Issue 42 (17th May 2017) - Zhu, Xiang; Li, Haining; Wang, Zheng; Yuan, Chaosheng; Zhu, Pinwen; Su, Lei; Yang, Kun; Wu, Jie; Yang, Guoqiang; Li, Xiaodong
Abstract : The phase behaviors of 1-dodecyl-3-methylimidazolium tetrafluoroborate ([C12 MIM][BF4 ]) had been investigated by means of Raman spectroscopy and polarized optical microscopy under pressure values up to 2.0 GPa at the temperature of 80.0 °C. Abstract : The phase behaviors of 1-dodecyl-3-methylimidazolium tetrafluoroborate ([C12 MIM][BF4 ]) had been investigated by means of Raman spectroscopy and polarized optical microscopy under pressure values up to 2.0 GPa at the temperature of 80.0 °C. Upon compression, change in the ratio of peak heights of symmetric and asymmetric CH2 stretching modes of Raman spectra in [C12 MIM][BF4 ] ( r (CH2 )ss/(CH2 )as ) indicated that it might experience two successive phase transitions. The structure evolution of the sample, which was investigated through the image analysis from polarized optical microscopy, was found to share many of the known quantitative properties of the smectic A phase of [C12 MIM][BF4 ]. These facts were suggestive of ionic liquid crystal induced by compression in [C12 MIM][BF4 ] under the pressure between 0.25 GPa to 0.60 GPa, which was similar to ionic liquid crystal upon cooling from its melt.